Precedent, commentary, and legal rules in the Madhhab-Law tradition: Ibn Quṭlūbughā's (d. 879/1474) al-Taṣḥīḥ wa-al-tarjīḥ - Al-Azem, T (2011)
This thesis examines the role that scholarly digests and commentaries played in the formation of legal rules in the Muslim legal institution known as the madhhab. I posit that a shared approach to legal rule-determination, and the respect of juristic precedent that it entails, underlies the jurisprudential processes of all of the four post-classical Sunni madhhabs (the Ḥanafī, Mālikī, Shāfi'ī, and Ḥanbalī), and unites them in a wider ‘madhhab-law tradition’. Taking the Ḥanafī madhhab as a case study, the thesis analyses a commentary written by the late Mamluk jurist Ibn Quṭlūbughā (d. 879/1474) upon the digest of the celebrated Abbasid-era Abū al-Ḥusayn al-Qudūrī (d. 428/1037). In discussing the madhhab's heritage of precedent, Ibn Quṭlūbughā's commentary weaves an intricate tapestry of quotations and references from previous jurists and works, providing us with insight into how author-scholars reacted to, and interacted with, other jurists over space and time. Chapter 1 provides a short introduction to the lives of Qudūrī and Ibn Quṭlūbughā, and the contexts within which they produced their works. Chapter 2 employs both quantitative and qualitative analysis of the commentary, in order to deduce historical and geographical patterns out of which a periodisation of rule-determination in the Ḥanafī madhhab is proposed. In Chapter 3, Ibn Quṭlūbughā's jurisprudential theory of rule-determination is studied, examining both the justifications and the processes employed by jurists in arriving at a legal rule in the Ḥanafī madhhab. Chapter 4 then turns to the craft of commentary itself, analysing over eighty case examples for the logical relationships, rhetorical devices, and legal arguments that inform the actual practice of rule-determination through commentary. A final chapter then summarises the conclusions, and situates them within a broader discussion as to the nature of the madhhab-law tradition.